CORRUPTION AS AN EXTRAORDINARY CRIME: EVALUATING THE RULE OF LAW, DEMOCRACY AND HUMAN RIGHTS - Litya Surisdani Anggraeniko; Reine Rofiana; Arie Kartika; Muh Farhan Arfandy; Muhyi Mohas (PT. Radja Intercontinental Publishing, 2026)
Corruption categorized as an extraordinary crime continues to show a significant upward trend in Indonesia. As a product of the 1998 reform movement, efforts to realize a clean government were institutionalized through Law Number 28 of 1999. However, empirical realities show a structural anomaly where democratic instruments are hijacked by old power structures acting as free riders to perpetuate authoritarian tendencies. This systemic failure degrades the rule of law and forces a critical re-examination of how political transitions accommodate oligarchic resilience. Consequently, this study addresses how corruption undergoes structural metamorphosis, how state capture interacts with democratic procedures, and to what extent it deprives citizens of constitutional protections. Research Method, using a combined legal research method (normative-empirical jurisprudence) with a qualitative-descriptive approach, this study dissects State Capture Corruption through Olle Törnquist’s